Privacy Protection Schemes in Internet of Vehicles (IoV): A Review and Analysis - Jiang, Zheng; Chua, Fang-Fang; Lim, Amy-Hui-Lan (International Journal of Membrane Science and Technology, 2023)
Internet of Vehicles (IoV) refers to a dynamic network of vehicles where data exchange is a way of communication among them. Existing work focus on mitigating the data leakage and strengthening the privacy protection during data exchange among vehicles in IoV, specifically on the Safety Beacon Message (SBM) as it contains location and identity of the vehicles. Limited work reported on the design of privacy protection schemes explicitly for SBM, and the success case studies in implementation of privacy protection schemes in various types of IoV architectures. This paper aims to review past research on privacy protection schemes for SBM in IoV architectures and the challenges in pursuing similar research in current environment. Firstly, this paper discusses the privacy protection issues related to SBM that arise in the centralized IoV architectures. Next, decentralization and tamper- proof features of blockchain in IOV is introduced as the enhancement to the centralized IoV architectures. Then, privacy protection issues related to SBM in a blockchain-based IoV architecture will be discussed. Finally, this paper concludes with future direction of work in privacy protection schemes in blockchain- based IoV architecture.